FIRST RECORD OF ICHTHYOSAURS IN SICILY(UPPER TRIASSIC OF MONTE SCALPELLO, CATANIA PROVINCE) (Rivista italiana di Paleontologia e Stratigrafia, 2014)
Here we report for the first time on the presence of ichthyosaurs in Sicily, southern Italy. The deposit of origin (Mufara Formation) can be dated to the upper Carnian (Tuvalian substage) based on a typical association of ammonites, one of which (Shastites sp.) is embedded in the sediment still encrusting one of the bone specimens recently found. The latter consist of two isolated vertebral centra that are referred to the Ichthyosauria thanks to their disk-like shape (i.e. they are much taller than long) combined with the amphicelous condition, lack of transverse processes, and presence of rib articulations on the central sides. The largest specimen is more precisely an anterior dorsal vertebra from an adult individual, ascribed to Shastasauridae indet. By the presence of elongated reniform diapophyseal facets, cranially not truncated, and absence of parapophyses. The smaller specimen represents an anterior cervical element from an immature individual of a likely smaller-sized, indeterminate taxon. These finds indicate that the biodiversity of the Monte Scalpello Triassic fauna is higher than previously known, but above all represent the southernmost occurrence of Triassic ichthyosaurs in the western Tethys basin.